Drosophila as a model for drug addiction - Heberlein, Ulrike (Henry Stewart Talks, 2008)
Behaviors induced by ethanol and cocaine in Drosophila, Genes and pathways that regulate ethanol-induced behaviors: amnesiac, and the cAMP/PKA and insulin pathways, Genes and neurons that regulate cocaine-induced behaviors: dlmo and the PDF-producing lateral neurons
Reviewed at 2017/09/25